Performance enhancement of a double slope solar still integrated with external condenser and internal heating system - Al-Ragehi, Haythem; Al-Qadami, Ebrahim; Ahsan, Amimul; Mohammad Razi, Mohd Adib; Shah, Syed Muzzamil Hussain; Aljaradin, Mohammad; Md Shafiquzzaman; Idrus, Syazwani; Imteaz, Monzur (John Wiley and Sons, 2025)
Solar energy has been a clean and renewable resource that offers a promising solution for water harvesting. Herein, a double slope solar still (DSSS) unified with an external condenser and internal heater was fabricated and tested to enhance freshwater production rates under Malaysian climate conditions. The integrated model was designed to operate both day and night, and its productivity was compared with that of a passive still. The study outcomes revealed that the average increment in the daily production rate of the active still was 56% during the daytime and 510% during the nighttime compared to the passive one. When calculating the cumulative production rates over the five days of the field experiment, the active still demonstrated a notable increase in productivity, reaching approximately 159% as compared to the passive one. This resulted in total production rates of 34.14 and 13.20 kg/m2 from the active and passive stills, respectively. Compared to the passive still, the active still had a lower relative humidity due to the external condenser. Additionally, the factors such as water and ambient temperatures and solar radiation intensity significantly impact daily distillate output at which strong correlations were observed between these parameters. Finally, the product water demonstrates a significant improvement in desalinated water quality, meeting safety standards outlined by the World Health Organization (WHO).